THE ROLE OF WATER IN THE FABRIC DYEING PROCESS FROM A SUSTAINABLE FASHION PERSPECTIVE - Faradillah Nursari; Arini; Gina Shobiro Takao (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2022)
Synthetic fabric dyes pollute rivers and other water sources due to poor waste management and the high demand to create fabric for the fast fashion industry. Although water is an essential source for fabric dyeing, the merit of water is contradictive in this point due to its role in dyeing fabric but having its source polluted. The subject of fabric dyes, their formulation, and their techniques were discussed the most in academia, not only in fashion but also in science. However, there needs to be more discussion regarding how fresh water became a primary material to create fabric dyes or dye the fabric itself. This study focuses on how water plays a significant role in the fabric dyeing process for the fashion industry and its impact on the environment. Qualitative methods applied in this research include data collection, such as a literature review. Citarum river and its watercourses became an example of how freshwater resources support the factories' production process in the fashion industry. Data collection is analyzed based on the sustainable theory applied in textile and fashion. Water was a significant primary material in the fabric dyeing process in this study. Furthermore, fresh water is needed to produce a coloured fabric using synthetic dyes. Additionally, there is a concern regarding waste treatment to avoid water pollution. Water waste from natural dyes does not pollute the environment and could be a better alternative to reduce water usage and pollution from synthetic dyes.